2016
DOI: 10.2298/jsc151124011y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of organics and heavy metals acute toxicities to Vibrio fischeri

Abstract: Vibrio fischeri bioluminescence inhibition has been widely used to test acute toxicities of metals and organics contaminants. However, the differences of metals and organics acute toxicities to V. fischeri have not been compared. Here, four heavy metals (Zn2+, Cu2+, Cd2+, Cr6+) and five organics (phenol, benzoic acid, p-hydroxy benzoic acid, nitro-benzene and benzene) acute toxicities to V. fischeri were investigated. Heavy metals toxicities to V. fischeri were increased along with the reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 25 publications
2
7
0
1
Order By: Relevance
“…These results are in agreement with those reported by Yang et al (2016), who investigated the acute toxicity of four heavy metals (Zn, Cu, Cd and Cr) using V. fischeri: they also showed that heavy metal toxicity to V. fischeri increased along with the reaction time. Utgikar et al (2004) studied the toxic effects of zinc and copper separately and in binary solution, and they observed qualitative and quantitative differences in the nature of the response, indicating possible different toxicity/inhibition mechanisms for zinc and copper as well as an enhancement of the toxic effect when both elements were in solution.…”
Section: Potential Ecotoxicological Effect Of Blue Lagoon Waterssupporting
confidence: 93%
“…These results are in agreement with those reported by Yang et al (2016), who investigated the acute toxicity of four heavy metals (Zn, Cu, Cd and Cr) using V. fischeri: they also showed that heavy metal toxicity to V. fischeri increased along with the reaction time. Utgikar et al (2004) studied the toxic effects of zinc and copper separately and in binary solution, and they observed qualitative and quantitative differences in the nature of the response, indicating possible different toxicity/inhibition mechanisms for zinc and copper as well as an enhancement of the toxic effect when both elements were in solution.…”
Section: Potential Ecotoxicological Effect Of Blue Lagoon Waterssupporting
confidence: 93%
“…Most of the microbial biosensors based on luminescent bacteria could be classified as this specific group (Belkin, 2003 ). Nowadays, biosensors are rapidly developing toward higher sensitivity, specificity, reproducibility, automation and high throughput (Conforti et al, 2008 ; Skotti et al, 2014 ; Yang et al, 2016 ). Furthermore, some specific biosensors with recombinant bioluminescent bacteria have also been designed to detect cell damage, like DNA damage, protein damage, cell membrane damage and stress response (Ahn et al, 2009 ; Sazykin et al, 2016 ; Jiang et al, 2017 ).…”
Section: Development Application Of Toxicity Assessment By Luminescenmentioning
confidence: 99%
“…Inevitably, the application of multicellular organisms exhibits the undesirable limitations of relatively longer operation time and higher cost. Therefore, microbial bioassays, especially with luminescent bacteria increased widely interests in the acute toxicity bioassays due to its operational simplicity, less time and cost consuming, higher sensitivity, specificity, and reproducibility (Conforti et al, 2008 ; Skotti et al, 2014 ; Yang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the analysis of the total amount of heavy metals is unable to represent the full environmental behaviors and ecological effects of heavy metals [ 11 ]. Numerous studies deal with risk effects of single metal types, while in reality the aquatic organisms are often exposed to mixtures of metals [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, bioluminescence inhibition assay has been widely used to test acute toxicities of metals. Based on previous studies, Vibrio fischeri bioluminescence inhibition bioassay (VFBIA) only provides information about the overall acute metal toxicity [ 11 , 17 , 19 ]. Direct assessment of the potential chronic effects of metals by applying naturally bioluminescence species is currently lacking.…”
Section: Introductionmentioning
confidence: 99%